2021
DOI: 10.3390/polym13030477
|View full text |Cite
|
Sign up to set email alerts
|

Micellar Drug Delivery Systems Based on Natural Biopolymers

Abstract: The broad diversity of structures and the presence of numerous functional groups available for chemical modifications represent an enormous advantage for the development of safe, non-toxic, and cost-effective micellar drug delivery systems (DDS) based on natural biopolymers, such as polysaccharides, proteins, and peptides. Different drug-loading methods are used for the preparation of these micellar systems, but it appeared that dialysis is generally recommended, as it avoids the formation of large micellar ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
85
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(86 citation statements)
references
References 169 publications
0
85
0
1
Order By: Relevance
“…Thus, micelles were an important addition to the middle ground between monophasic and biphasic systems, which apparently paved the way for the modern era of nanoscience. Over a century or so since its inception, the micelle concept has evolved in sophistication beyond the original aims concerning surfactants and detergency, with recent applications [15][16][17][18] being directed towards vesicles, drug delivery systems, etc.…”
Section: The Nature Of the Micellar Phasementioning
confidence: 99%
“…Thus, micelles were an important addition to the middle ground between monophasic and biphasic systems, which apparently paved the way for the modern era of nanoscience. Over a century or so since its inception, the micelle concept has evolved in sophistication beyond the original aims concerning surfactants and detergency, with recent applications [15][16][17][18] being directed towards vesicles, drug delivery systems, etc.…”
Section: The Nature Of the Micellar Phasementioning
confidence: 99%
“…Importantly, dextran is a kind of FDA-approved natural polymer. Several studies have reported the use of dextran and its derivatives as nanocarriers for cancer imaging and therapy [ 26 , 27 , 28 , 29 , 30 ]. Herein, we prepare a novel pH and reduction dual-sensitive polymeric prodrug oDex-g-Pt+DOX, in which Pt (IV) prodrug was conjugated to the oxidized dextran (oDex) as reduction-sensitive segment, and then DOX was conjugated via acid-cleavable hydrazone bond ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Polymers exhibiting a UCST have been studied for the development of drug delivery systems to release therapeutics under hyperthermic conditions [ 9 ]. In contrast, LCST-polymers come in a wider variety and comprise synthetic polymers such as poly( N -isopropylacrylamide) (PNIPAM) [ 10 ], the most extensively studied LCST-polymer, but also poly(oligo ethylene glycol methacrylate) (P(OEGMA)) [ 11 ], poly(2-oxazoline) (POx) [ 12 ], polypeptoids [ 13 ], poly(N-vinylcaprolactam) [ 14 ] and certain block copolymers [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%